Forensic Radiology in the Detection of Internal Gynecological Trauma following Alleged Assault. A Cross-Sectional Study - Farhat Sultana, Sajjad Ul Hasan, Ayesha Rana, Abdul Waheed, Safia Ashraf, Mahwash Mansoor, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Sexual assault is a serious medico-legal and public health concern. Internal gynecological injuries often go undetected during routine clinical examinations due to their concealed nature and patient distress. Forensic radiology offers a non-invasive, objective method to identify and document such trauma. Objective: To assess the effectiveness of forensic radiology in detecting internal gynecological trauma in women presenting with alleged sexual assault. Methods: A cross-sectional study was conducted from January 2022 to February 2023 at the Department of Forensic Medicine, Allama Iqbal Medical College/Jinnah Hospital Lahore, and Karachi Institute of Medical Sciences (KIMS), Malir Cantt, Karachi. A total of 70 female victims aged 15–45 years underwent clinical examination followed by transabdominal ultrasound, transvaginal ultrasound (where permissible), and MRI in selected cases. Findings from clinical and radiological assessments were compared. Results: Internal injuries were detected in 67.1% of cases through imaging, while clinical examination alone identified injuries in 41.4% of cases. MRI was particularly effective in identifying deep injuries such as uterine contusions and broad ligament hematomas. In 31.4% of cases, injuries were diagnosed exclusively via radiology. Conclusion: Forensic radiology, particularly ultrasound and MRI, significantly enhances the detection and documentation of internal gynecological injuries in sexual assault cases and should be integrated into standard medico-legal protocols. Keywords: Forensic radiology, sexual assault, gynecological trauma, MRI, medico-legal imaging.